Doping in sport: The case of fencing - Luczak, M. (Central European Journal of Sport Sciences and Medicine, 2016)
Most athletes in order to achieve satisfactory results have to train long and hard. However, some of them, aiming at victory at all costs, resort to doping. The benefits of winning are relatively small when compared to the damage of the human organism caused by doping. The phenomenon has been present in cycling, athletics, boxing, football, weightlifting and many other sport disciplines for many years. In fencing only few instances of the use of illegal substances during the competition were revealed, which was reflected in Polish and foreign sports press. In many European countries the use of doping is regulated by the anti-doping rules, regulations and policies that define these practices as penal acts. In Poland the problem of doping was first regulated by the Act on Physical Culture of 1984 and 1996 as well as the he Act of 1985 on Prevention of Drug Abuse. The regulations of FIE fencing competitions, prepared on the request of Polish Fencing Federation on the basis of the FIE competition rules in the disciplinary regulations of competitions prohibited the use of artificial stimulants during or before the competition. The aim of this paper is to present the threats in modern sports with particular attention to the phenomenon of doping in fencing, as well as in social terms. It is a case study and a study of selected issues connected to doping in contemporary sports. The author poses the question whether the fencers often are tempted to support their bodies with doping in order to achieve better results than the representatives of other sports? What percentage of the fencers were using illegal stimulants? Is there is a problem of doping in fencing, and if so, what is its scale?